First to Be Judged, Last to Resist: Rejection Sensitivity and Assertiveness Challenges of Firstborn Daughters in Indonesia’s High-Stakes Workplaces - Gomargana, Chrysan (Flourishing Journal, 2025)
This study investigates how rejection sensitivity (RS) predicts assertiveness difficulties among firstborn daughters in Indonesia’s high-pressure workplaces, and how workplace context moderates this relationship. A total of 268 participants (M = 27.6, SD = 4.1) completed measures of RS (Adult Rejection Sensitivity Questionnaire; α = .87), assertiveness difficulty (Functional Assertiveness Scale; α = .81), and workplace pressure (α = .84 - .86). Moderated regression analysis indicated that RS significantly predicted assertiveness difficulty (B = 0.49, SE = 0.07, t(264) = 6.98, p < .001). The RS × workplace pressure interaction was also significant (B = 0.22, SE = 0.08, t(264) = 2.75, p = .006). Simple slopes analyses revealed that the RS–assertiveness link was stronger under high workplace pressure. Findings suggest that compliance behaviors may emerge as adaptive self-silencing shaped by RS, cultural expectations, and organizational climate, underscoring the importance of fostering psychological safety and structured voice opportunities in organizations. AbstrakPenelitian ini mengkaji bagaimana sensitivitas penolakan (RS) memprediksi kesulitan asertivitas di kalangan anak perempuan sulung di tempat kerja yang bertekanan tinggi di Indonesia, serta bagaimana konteks tempat kerja memoderasi hubungan ini. Sebanyak 268 peserta (M = 27.6, SD = 4.1) mengisi instrumen pengukuran RS (Adult Rejection Sensitivity Questionnaire; α = .87), kesulitan asertivitas (Functional Assertiveness Scale; α = .81), dan tekanan tempat kerja (α = .84/.86). Analisis regresi dimoderasi menunjukkan bahwa RS secara signifikan memprediksi kesulitan asertivitas (B = 0.49, SE = 0.07, t(264) = 6.98, p < 0.001). Interaksi antara RS dan tekanan tempat kerja juga signifikan (B = 0.22, SE = 0.08, t(264) = 2.75, p = 0.006). Analisis lereng sederhana menunjukkan bahwa hubungan antara RS dan asertivitas lebih kuat di bawah tekanan tempat kerja yang tinggi. Temuan ini menyarankan bahwa perilaku kepatuhan mungkin muncul sebagai penekanan diri yang adaptif yang dibentuk oleh RS, ekspektasi budaya, dan iklim organisasi, menyoroti pentingnya memupuk keamanan psikologis dan peluang suara yang terstruktur dalam organisasi.